Mass, media, laws and regulations in India - Iyer, Venkat (Ed.) (Singapore Asian Media for Information and Communication Centre, 2000)
Mass,media,laws and regulations in India published by Asian Media Information and Communication Centre.The main contents of the book are-Radio and Television,Film and Video,Internet,Dramatic performance,Broadcasting bill,Cable television networks,Press Co
Keywords: Mass media-Laws and legislation